Health Care Benchmarking and Performance Evaluation An Assessment using Data Envelopment Analysis (DEA) - Ozcan, Yasar A.; SpringerLink (Online service) (Boston, MA : Springer US : Imprint: Springer, 2014)
This new edition continues to emphasize the use of data envelopment analysis (DEA) to create optimization-based benchmarks within hospitals, physician group practices, health maintenance organizations, nursing homes, and other health care delivery organizations. Suitable for graduate students learning DEA applications in health care as well as for practicing administrators, it is divided into two sections covering methods and applications. Section I considers efficiency evaluations using DEA; returns to scale; weight restricted (multiplier) models; non-oriented or slack-based models, including in this edition two versions of non-controllable variable models and categorical variable models; longitudinal (panel) evaluations; and the effectiveness dimension of performance evaluation. A new chapter then looks at new and advanced models of DEA, including super-efficiency, congestion DEA, network DEA, and dynamic network models. Mathematical formulations of various DEA models are placed in end-of-chapter appendices. Section II then looks at health care applications within particular settings, chapter-by-chapter, including hospitals, physician practices, nursing homes, and health maintenance organizations (HMOs). Other chapters then explore home health care and home health agencies; dialysis centers, community mental health centers, community-based your services, organ procurement organizations, aging agencies, and dental providers; DEA models to evaluate provider performance for specific treatments, including stroke, mechanical ventilation, and perioperative services. A new chapter then examines international-country-based applications of DEA in health care in 16 different countries, along with OECD and multi-country studies. Most of the existing chapters in this section were expanded with recent applications. Included with the book is online access to a learning version of DEA Solver software, written by Professor Kaoru Tone, which can solve up to 50 DMUs for various DEA models listed in the User$1 (Bs Guide at the end of the book.s
Section I: Methods -- Chapter 1 Evaluation of Performance in Health Care -- Chapter 2 Performance Measurement Using Data Envelopment Analysis (DEA) -- Chapter 3 Returns To Scale Models -- Chapter 4 Weight Restricted (Multiplier) Models -- Chapter 5 Non-Oriented and Measure Specific Models -- Chapter 6 Longitudinal (Panel) Evaluations Using DEA -- Chapter 7 Effectiveness Dimension of Performance -- Chapter 8 Advanced DEA Models -- Section II: Applications -- Chapter 9 Hospital Applications -- Chapter 10 Physician Practice and Disease Specific Applications -- Chapter 11 Nursing Home Applications -- Chapter 12 Health Maintenance Organization (HMO) Applications -- Chapter 13 Home Health Agency Applications -- Chapter 14 Applications for Other Health Care Organizations -- Chapter 15 Other DEA Applications in Hospital Settings -- Chapter 16 International-Country Based DEA Health Studies.
Keywords: Economics; Practice of medicine; Operations research; Economics/Management Science; Operation Research/Decision Theory; Health Administration; Operations Research, Management Science